The effects of some cryptogamic extracts on the primary productivity of Vigna unguiculata L. Walp - P. O. Fatoba; O. Rebecca Akolo (Advances in Aquaculture and Fisheries Management, 2020)
The effect of hot and cold aqueous extracts of Barbula lambarenensis, Dryopteris flix-max; Nephrolepis davalloides, Phymatodes scolopenta, Platycerium angolense and Azadrachta indica and Karate 2.5EC (chemical) on the primary productivity of cowpea were investigated. The extracts of the plant materials and the chemical were appropriately used to irrigate the cowpea twice a week during flowering. The number of pods per plant, length of pods, number of seeds per pod, number of seeds per plant, filling potentials and the weight of seeds per plant were determined for each of the 14 regimes. It was found that all the treatments other than cold extracts of B. lambarenensis, extracts of Dryopteris and Nephrolepis showed better performance than the untreated in the measured variables. Cowpea treated with hot aqueous B. lambarenensis extracts, hot and cold extracts of P. scolopenta, P. angolense and A. indica compared favourably and even better than the one treated with Karate 2.5EC (Lambda – cyhalothrin), a universally used chemical. This shows that these plants can serve as good materials or alternatives to Karate and can therefore be integrated into use for the production of cowpea.